An evaluation of heat loss on top of solar collector with multilayered absorber in solar water heating system - M., Norfahana; Ismail, Ahmad Faris; Majid, Z. A. A. (Asian Research Publishing Network (ARPN), 2016)
Solar water heating system is one of the applications of solar energy. One of the components of solar water heating system is solar collector that consists of an absorber. The heat loss to the surroundings is in important factor in the determination of performance of the solar collector. The smaller value of heat losses to the surrounding will result the higher performance of the solar collector. Thus, this study is conducted to evaluate the heat loss of top of solar collector with multilayered absorber in solar water heating system. Methods used in this paper include solar collector with multilayered absorber is tested and evaluated by examining the heat loss at top of solar collector in solar water heating system. The results show the impact to the solar water heating system is indeed predictable where multilayered absorber in solar collector is proven to play its main role when it able to keep the hot water temperature longer at minimum amount of 176.4 W/unit area as for heat loss.